2016
DOI: 10.1371/journal.pone.0145928
|View full text |Cite
|
Sign up to set email alerts
|

Production and Identification of Wheat-Agropyron cristatum 2P Translocation Lines

Abstract: Agropyron cristatum (L.) Gaertn. (2n = 28, PPPP), a wild relative of common wheat, possesses many potentially valuable traits that can be transferred to common wheat through breeding programs. The wheat-A. cristatum disomic addition and translocation lines can be used as bridge materials to introduce alien chromosomal segments to wheat. Wheat-A. cristatum 2P disomic addition line II-9-3 was highly resistant to powdery mildew and leaf rust, which was reported in our previous study. However, some translocation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…This conclusion is also supported by the phylogenetic analysis between P and the wheat A, B, and D genomes (Figure 4 ). These results were the first to reveal the evolutionary relatedness between A. cristatum and the wheat A, B, and D genomes and explained that the wheat A genome and B genome had a higher number of chromosome arrangements with A. cristatum chromosomes than the D genome (Badaeva et al, 2007 ; Li et al, 2016 ). Interestingly, the variant density in the transcriptional regions was relatively lower in the telomeric and centromeric regions than that in the other chromosomal regions (Figure 6G ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This conclusion is also supported by the phylogenetic analysis between P and the wheat A, B, and D genomes (Figure 4 ). These results were the first to reveal the evolutionary relatedness between A. cristatum and the wheat A, B, and D genomes and explained that the wheat A genome and B genome had a higher number of chromosome arrangements with A. cristatum chromosomes than the D genome (Badaeva et al, 2007 ; Li et al, 2016 ). Interestingly, the variant density in the transcriptional regions was relatively lower in the telomeric and centromeric regions than that in the other chromosomal regions (Figure 6G ).…”
Section: Discussionmentioning
confidence: 89%
“…Although the wheat- A. cristatum derivatives represent an attractive source of value-added traits (Zhang et al, 2015b ; Li et al, 2016 ), the genetic relationship and variants, which represent the fundamental key to breeding success and provide a basis for breeders to select varieties with a constantly improving yield performance (Bedő and Láng, 2015 ), of A. cristatum compared to wheat at the molecular level remain unknown. This study showed that A. cristatum had abundant genetic resources and diversity compared to wheat from the various aspects described below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a set of additional wheat– A. cristatum lines and disomic substitution lines were produced and characterized (Han et al ., ; Wu et al ., ), some of which will be valuable for future wheat breeding as novel germplasms (Chen et al ., ; Wu et al ., ). For example, the 6P disomic addition line 4844 shows high yield characteristics for the number of florets and kernels per spike compared with those of its wheat parent (Li et al ., ; Wu et al ., ), and resistance to powdery mildew and leaf rust was transferred from A. cristatum to common wheat (Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Among these EST-STS markers, 6063 can be used in the identification of wide crosses in the single-receipt Fukuho parent background, and 3070 A. cristatum- specific markers in eight wheat variety backgrounds can be applied to molecular marker-assisted selection of A. cristatum introgressions into commercial varieties. In the present study, these markers have been applied successfully for the physical mapping of 2P, 6P and 7P alien chromatin fragments in A. cristatum –wheat introgression lines 27 , 30 , 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%